1984
DOI: 10.1021/ma00141a011
|View full text |Cite
|
Sign up to set email alerts
|

Photosensitized degradation of polystyrene by benzophenone in benzene solution

Abstract: Photodegradation of polystyrene in benzene solution sensitized by benzophenone was studied at 60 °C by measuring the rate of benzophenone disappearance and the change in GPC curves of polystyrene during 365-nm irradiation by a high-pressure mercury lamp. Various rate constants for the initiation step were determined by quantum yield and transient lifetime measurements. The quantum yield of benzophenone photoreduction, (_ ), is 0.0086-0.0035 for [PS] = 0-0.2 unit-M and decreases with increasing polystyrene conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

1996
1996
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 6 publications
1
26
0
1
Order By: Relevance
“…Photoinduced damage in dye-doped polymer matrices has been studied in various systems for different applications [85][86][87][88][89][90][91][92][93][94]. Sensitized photodegradation and photooxidation of polymers can be induced by photoinitiators, in which polymer degradation or oxidation can be initiated by free radicals originating from photodegradation of sensitizers; or by photosensitizers, in which excited sensitizers transfer energy to the polymer or oxygen to initiate photodegradation or photooxidation [85].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photoinduced damage in dye-doped polymer matrices has been studied in various systems for different applications [85][86][87][88][89][90][91][92][93][94]. Sensitized photodegradation and photooxidation of polymers can be induced by photoinitiators, in which polymer degradation or oxidation can be initiated by free radicals originating from photodegradation of sensitizers; or by photosensitizers, in which excited sensitizers transfer energy to the polymer or oxygen to initiate photodegradation or photooxidation [85].…”
Section: Introductionmentioning
confidence: 99%
“…Sensitized photodegradation and photooxidation of polymers can be induced by photoinitiators, in which polymer degradation or oxidation can be initiated by free radicals originating from photodegradation of sensitizers; or by photosensitizers, in which excited sensitizers transfer energy to the polymer or oxygen to initiate photodegradation or photooxidation [85]. Studies on photooxidation or photodegradation of various sensitized polymers have been reported including sensitized PS [85][86][87][88] and sensitized PMMA [89,90]. Laser ablation of polymers can be induced with the assistance of photosensitizers using visible lasers at wavelengths of 351 nm [91], 488 nm [92], and 532 nm [93].…”
Section: Introductionmentioning
confidence: 99%
“…These radicals can combine to form a C‐C bond. The photodegradation of polystyrene when irradiated in air for several hours has been well documented . The photodegradation was reduced by irradiating only for short periods of time (15–30 min).…”
Section: Resultsmentioning
confidence: 99%
“…The photodegradation of polystyrene when irradiated in air for several hours has been well documented. [24][25][26] The photodegradation was reduced by irradiating only for short periods of time (15-30 min). Also, the high concentration of BP directly on top of the PS fi lm can compete with the polymer chain scission and favor BP and PS radical coupling.…”
Section: Resultsmentioning
confidence: 99%
“…[ 64 ] The radical on PS can then undergo β‐scission to release an α‐alkylstyrene product and form another benzylic radical on PS (Figure 17c). [ 64 ] The radical on PS can also abstract a hydrogen atom from another PS methine position to propagate the radical chain process. [ 64 ] Alternatively, chain termination or crosslinking can occur to stop the PS degradation.…”
Section: Non‐thermal Upcyclingmentioning
confidence: 99%